Effect of Different Substrate Temperatures on Microstru- cture and Residual Stress of Ti Films. Issue 4 (April 2016) - Dong, Meiling; Cui, Xiufang; Wang, Haidou; Zhu, Lina; Jin, Guo; Xu, Binshi
Abstract: The influence of different substrate temperatures of Ti film prepared by the direct current (DC) magnetron sputtering on the internal residual stress of Ti film were investigated experimentally by nanoindentation technique including Suresh model and Lee model. The results of the nanoindentation method and the curvature method were compared. At the same time, the surface morphology and the microstructure of Ti film were analyzed using atomic force microscope (AFM) and X-ray diffraction (XRD). The results show that the residual stress value obtained by Suresh model is almost the same as that by the curvature method, so the Suresh model is more suitable for calculating the residual stress of Ti films. Together with the nanoindentation data and micro-structure analysis, it is found that with the substrate temperature rising, the grain size of Ti films increases first and then decreases; the residual stress of the Ti film changes from the compressive stress to the tensile stress.